OpenStack Swift using, administering, and developing for Swift object storage - Arnold, Joe (O'Reilly, 2015)
Get up and running with OpenStack Swift, the free, open source solution for deploying high-performance object storage clusters at scale. In this practical guide, Joe Arnold, co-founder and CEO of SwiftStack, brings you up-to-speed on the basic concepts of object storage and walks you through what you need to know to plan, build, operate, and measure the performance of your own Swift storage system. Object storage is essential today with the growth of web, mobile, and software-as-a-service (SaaS) applications. This book helps you through the process, with separate sections on application deve.
Includes index. - Online resource; title from PDF cover (ebrary, viewed October 28, 2014)
Keywords: Storage area networks (Computer networks); Cloud computing; Réseaux de stockage (Informatique); Infonuagique; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference